Factfulness - Rosling, Hans; Rosling, Ola; Ronnlund, Anna Rosling (Great Britain : Sceptre, 2018)
Timely, short and essential, FACTFULNESS reveals the power of facts in a post-truth world, by late international sensation Hans Rosling ('a true inspiration' - Bill Gates) and his long-term collaborators Ola and Anna.
Keywords: Forecasting